ANALYSIS OF FACTORS INFLUENCING THE IMPLEMENTATION OF MINING SAFETY MANAGEMENT SYSTEM (SMKP) & OHS MANAGEMENT SYSTEM (SMK3) BASED ON THE PRINCIPLE OF RESILIENCE AT PT. MITRA SETIA TANAH BUMBU - Ronny Ronald Simamora; Erislan, Erislan; Ramli, Soehatman (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
In mining activities, Occupational Safety and Health is an ongoing process involving the parties within the organization, so that each company is required to implement a Mining Safety Management System to create conducive conditions, so that it is free from danger and risk. To strive to improve the performance of Occupational Safety and Health and the company's Environment, one of the efforts made is the implementation of SMKP and SMK3, because through the existing system in mining in Indonesia, it can reduce the rate of mining accidents. Based on the results of the analysis of the perception of the Safety Maturity Level of workers, an average score of 4.1 was obtained and it was included in the proactive category. The results of the 2023 SMKP Audit showed that the percentage of achievement of PT MSTB's implementation was 50.89%, included in the